Delirium in the Emergency Department and Its Extension into Hospitalization (DELINEATE) Study: Effect on 6‐month Function and Cognition. Issue 6 (6th March 2017) - Han, Jin H.; Vasilevskis, Eduard E.; Chandrasekhar, Rameela; Liu, Xulei; Schnelle, John F.; Dittus, Robert S.; Ely, E. Wesley
Abstract : Background: The natural course and clinical significance of delirium in the emergency department (ED) is unclear. Objectives: We sought to (1) describe the extent to which delirium in the ED persists into hospitalization (ED delirium duration) and (2) determine how ED delirium duration is associated with 6‐month functional status and cognition. Design: Prospective cohort study. Setting: Tertiary care, academic medical center. Participants: ED patients ≥65 years old who were admitted to the hospital. Measurements: The modified Brief Confusion Assessment Method was used to ascertain delirium in the ED and hospital. Premorbid and 6‐month function were determined using the Older American Resources and Services Activities of Daily Living (OARS ADL) questionnaire which ranged from 0 (completely dependent) to 28 (completely dependent). Premorbid and 6‐month cognition were determined using the short form Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) which ranged from 1 to 5 (severe dementia). Multiple linear regression was performed to determine if ED delirium duration was associated with 6‐month function and cognition adjusted for baseline OARS ADL and IQCODE, and other confounders. Results: A total of 228 older ED patients were enrolled. Of the 105 patients who were delirious in the ED, 81 (77.1%) patients' delirium persisted into hospitalization. For every ED delirium duration day, the 6‐month OARS ADL decreased by 0.63 points (95% CI: −1.01 to −0.24), indicating poorer function. For every ED delirium duration day, the 6‐month IQCODE increased 0.06 points (95% CI: 0.01–0.10) indicating poorer cognition. Conclusions: Delirium in the ED is not a transient event and frequently persists into hospitalization. Longer ED delirium duration is associated with an incremental worsening of 6‐month functional and cognitive outcomes.